Understanding Climate Displacement in Nepal: A Qualitative Look through the Story of Samjung - Gurung, Namrata Grace (NPRC Journal of Multidisciplinary Research, 2025)
This research paper explores the emerging crisis of climate induced displacement in Nepal, with qualitative focus on the village of Samjung in Upper Mustang. As climate change accelerates glacial retreat and disrupts traditional water sources, Himalayan communities face existential threats that go beyond loss of livelihood impacting the cultural identity, ancestral heritage and mental well-being. Drawing from the secondary data including government reports, climate studies and media documentation the study highlights how environmental shifts have forced Samjhung inhabitants to relocate amplifying a broader trend in the Himalayas. The paper critiques the current adaptation policies and emphasizes the urgent need for culturally sensitive, community centered climate resilience strategies. By studying Samjung this research aims to contextualize the broader perspective of Nepal’s vulnerability to climate change and advocate for urgent action at both national and international level.